Science and development of muscle hypertrophy - Schoenfeld, Brad 1962- (Human Kinetics, 2016)
Muscle hypertrophy -- defined as an increase in muscular size -- is one of the primary outcomes of resistance training. Science and Development of Muscle Hypertrophy is a comprehensive compilation of science-based principles to help professionals develop muscle hypertrophy in athletes and clients. With more than 825 references and applied guidelines throughout, no other resource offers a comparable quantity of content solely focused on muscle hypertrophy. Readers will find up-to-date content so they fully understand the science of muscle hypertrophy and its application to designing training programs. Written by Brad Schoenfeld, PhD, a leading authority on muscle hypertrophy, this text provides strength and conditioning professionals, personal trainers, sport scientists, researchers, and exercise science instructors with a definitive resource for information regarding muscle hypertrophy -- the mechanism of its development, how the body structurally and hormonally changes when exposed to stress, ways to most effectively design training programs, and current nutrition guidelines for eliciting hypertrophic changes. The full-color book offers several features to make the content accessible to readers: -- Research Findings sidebars highlight the aspects of muscle hypertrophy currently being examined to encourage readers to re-evaluate their knowledge and ensure their training practices are up to date. -- Practical Applications sidebars outline how to apply the research conclusions for maximal hypertrophic development. -- Comprehensive subject and author indexes optimize the book's utility as a reference tool. -- An image bank containing most of the art, photos, and tables from the text allows instructors and presenters to easily teach the material outlined in the book. Although muscle hypertrophy can be attained through a range of training programs, this text allows readers to understand and apply the specific responses and mechanisms that promote optimal muscle hypertrophy in their athletes and clients. It explores how genetic background, age, sex, and other factors have been shown to mediate the hypertrophic response to exercise, affecting both the rate and the total gain in lean muscle mass. Sample programs in the text show how to design a three- or four-day-per-week undulating periodized program and a modified linear periodized program for maximizing muscular development.